NKL-24 exerts potent antimicrobial and antibiofilm effects against Clostridium perfringens and reduces required level of sodium nitrite in pork sausage - Dian Dai; Jicheng Chen; Ning Guan; Yang Li; Shuqi Zhang; Bing Shao; Zhongguo Shan; Haihua Wang (Food Control, 2027)

A bibliometrics review of non-CO2 greenhouse gas reduction strategies - Yi-Ming Wei; Si-Yu Liu; Li-Jing Liu; Lan-Cui Liu; Qiao-Mei Liang; Xiao-Chen Yuan; Hong-Dian Jiang; Pallav Purohit; Felix Creutzig; Hua Liao; Biying Yu (Energy and Climate Change, 2026)

AUF1 modulates cellular senescence in auditory hair cells by regulating the transcription and alternative splicing of immune response genes - Lihua Li; Yun Xiao; Xingrui Liu; Jinying He; Wenjing Wu; Dian Cai; Xubo Chen (Molecular Biology Reports, 2026)

Targeting ACTG1 alleviates isoproterenol-induced cardiac injury by regulating endothelial-to-mesenchymal transition - Xianghui Zeng; Dian Wang; Hao Yang; Canqun Li; Ting Xiong; Ting Lu; Lu Dai; Feng Chen; Zhenfang Liu; Xing Li (Journal of Molecular Histology, 2026)

A multi-task learning model integrating physical property databases and multidimensional descriptors for predicting thermophysical properties of type III and V deep eutectic solvents and assisting screening - Dian Jin; Xindi Feng; Jiale Niu; Jiongyi Chen; Zuoxiang Zeng; Zhen Liu; Tao Li; Li Sun (Journal of Cleaner Production, 2026)

A multispectral and LC–MS/MS approach for investigating matrix interference in aflatoxin B1 analysis of pressed peanut cake - Mohan Li; Chenhao Jiang; Dian Zhou; Kewei Chen; Muying Du; Zsolt Zalán; Sameh Awad; Jianquan Kan (Food Chemistry, 2026)

Distribution characteristics and influencing factors of active cytomegalovirus infection in patients with hematological malignancies complicated with sepsis - Bingrong Chen; Shipeng Li; Wenxiu Shu; Jing Le; Xingfei Wang; Xiaoqi Ma; Guanguan Wei; Qiaoqiong Feng; Qing Li; Xiaodong Li; Dian Jin (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Canopy architecture drives productivity of subtropical Pinus massoniana mixed forests by modulating Solar Radiation using an integrated UAV and terrestrial LiDAR - Dasui Li; Yuzhong Chen; Junze Wan; Yujie Zhu; Yuanyong Dian; Jingjing Zhou (Agricultural and Forest Meteorology, 2026)

Sustainable solidification/stabilization of chromium (VI)-contaminated soil using enzyme-carbonated reactive magnesia cement: a novel eco-friendly approach - Min Shi; Dian-Long Wang; Jin-Yu Shi; Wen-Bo Chen; Hai-Long Li; Yue-Suo Yang; Chao-Sheng Tang (Journal of Environmental Management, 2026)

Sabulicella flocculans sp. nov., a Floc-Forming Bacterium of the Genus Sabulicella Isolated from Activated Sludge - Ansi Jiang; Xinjing Du; Yaqi Liu; Dian Jiao; Han Chen; Xin Wang; Yong Zhang; Shanhui Wang; Wei Li; Haiyan Zeng; Yan Huang; Dongru Qiu (Current Microbiology, 2026)

A deep stacked autoencoder for magnetotelluric data denoising via end-to-end time-domain noise mapping - Jin Li; Jingkun Ye; Nianchun Li; Dian Hong; Chaojian Chen (Journal of Applied Geophysics, 2026)

Engineering of Azotobacter chroococcum enables potential replacement of synthetic nitrogen fertilizer and mitigation of nitrogen pollutants release under medium-fertility field conditions - Ping Tian; Jun-Feng Wang; Dao-Yuan Wang; Yu-Dian Xun; Xiao-Hui Shi; Ming-Zhu Chen; Yun-Ying Liang; Mei-Ting Yang; Qu-Sheng Li (Bioresource Technology, 2026)

Characterization of dynamic behavior of clay-gravel mixtures under high cyclic strains in undrained triaxial conditions - Qiming Chen; Shun Wang; Dian-Qing Li; Wenqi Du (Soil Dynamics and Earthquake Engineering, 2026)

Understanding public perceptions of cultural ecosystem services in urban coastal wetland ecological restoration areas: A social media-based large language model approach - Zirui Zhao; Zhiyuan Ma; Bin Chen; Ping Li; Weiwei Yu; Wenjia Hu; Dian Zhang; Jianji Liao (Journal of Environmental Management, 2026)

First Report on the Asexual Morphology of Nigrograna jinghongensis (Nigrogranaceae, Pleosporales) with a New Host Record from China - Li‐Xue Mi; Hai‐Yan Song; Kevin D. Hyde; Prapassorn D. Eungwanichayapant; Ausana Mapook; Mu‐Sen Chen; Dian‐Ming Hu (New Zealand Journal of Botany, 2026)
Nigrograna jinghongensis was originally described based on sexual morphology from decaying woody litter in Yunnan Province, China. In this study, we report its asexual morph, isolated as endophytes from Tetradium ruticarpum in Anhui Province. The asexual morph of N. jinghongensis features coelomycetous pycnidia that are dark brown and globose to pyriform, bearing filiform, septate conidiophores with phialidic, hyaline conidiogenous cells, and ellipsoidal to subcylindrical, aseptate, guttulate conidia. Species identification was confirmed by multigene phylogenetic analysis using ITS, LSU, SSU, tef1‐α , and rpb2 sequences. This is the first report of the asexual morph of N. jinghongensis , expanding knowledge of its life cycle, ecological adaptability, and host association.

An innovative modified coal gangue capable of improving sandy soil remediation, wheat growth and drought resistance - Tian Tang; Shu Wu; Dian Li; Hongye Ma; Zheng Wang; Liuzhou Chen; Sanghoon Kim; Yajun Wang; Yangsheng Liu (Chemical Engineering Journal, 2026)

Amazonite as a cultural and technological marker: insights from the Dongshantou archaeological site in Jilin, China (2500 − 2000 BP) - Dian Chen; Xiaoming Wang; Xiaoxuan Shi; Di Zhang; Chao Li; Wugan Luo (Archaeological and Anthropological Sciences, 2026)

Brachymonas moutaii sp. nov., a floc-forming bacterium isolated from a distillery wastewater treatment plant - Yaqi Liu; Hui Wang; Ansi Jiang; Junmei Wu; Bi Chen; Yong Zhang; Siliang Yuan; Yan Huang; Haiyan Zeng; Xin Wang; Dian Jiao; Wei Li; et al. (Antonie van Leeuwenhoek, 2026)

METTL14 promotes ferroptosis during the development of cisplatin-induced kidney injury by stabilizing ERFE through IGF2BP3-dependent m6A methylation - Yan Chen; Wenlong Li; Dian Zhao; Chong Huang; Chengyun Xu (Journal of Trace Elements in Medicine and Biology, 2025)

Microbial community assembly driven by dissolved organic matter and sulfate induces arsenic transformation in shallow aquifers of lateritic red soil regions - Ming-Zhu Chen; Jun-Feng Wang; Jian-Ping Ouyang; Yi-Rong Deng; Mei-Ting Yang; Yu-Dian Xun; Xiao-Hui Shi; Guang-Yong Tang; Jian-Ying Mo; Han-Jie Ye; Qu-Sheng Li (Journal of Hazardous Materials, 2025)

Architectural design of multidimensional carbonaceous structures: Synergistic pathways enabling high-energy silicon-based anodes - Wendi Chen; Lingjun Guo; Ruonan Zhang; Guangyao Liu; Yue Ma; Dian Jia; Hejun Li; Keyu Xie (Chemical Engineering Journal, 2025)

Enhanced production of eicosapentaenoic acid and fucoxanthin in Phaeodactylum tricornutum via a two-stage strategy with multifactorial synergistic effects - Xin Dong; Meng-Han Zhao; Chen-Xi Li; Xiao Lin; Ning Ma; Hong-Jin Qiao; Dian-Feng Han; Ying-Jiang Xu (Journal of Applied Phycology, 2025)

Enhanced CO2 electrolysis via H2/CH4 assistance in a symmetric solid oxide electrolysis cell with an alloy-perovskite composite electrode - Shuangzhen Li; Feiya He; Jing Yan; Yawei Li; Si-Dian Li; Huili Chen (Chemical Engineering Journal, 2025)

Sensitive colorimetric assay for the detection of aflatoxin B1 via target-induced generation of multivalent DNA nanowires accelerates the catalytic hairpin assembly reaction - Shihong Zhang; Yingying Sun; Xingyu Liu; Cong Chen; Yuhan Ma; Dian Yu; Wenjie Liu; Jianna Yu; Guoxing Jing; Wen Liu; Wenshan Li (Analytica Chimica Acta, 2025)

Modified coal gangue enables synchronous sandy soil remediation and safe potato production: Efficacy and mechanisms - Tian Tang; Zheng Wang; Liuzhou Chen; Shu Wu; Dian Li; Hongye Ma; Sanghoon Kim; Yajun Wang; Yangsheng Liu (Journal of Cleaner Production, 2025)

Characterization of microbial consortium for rice straw degradation and the role of nitrogen sources in community assembly - Liuzhou Chen; Tian Tang; Dian Li; Zheng Wang; Shu Wu; Yangsheng Liu (Chemical Engineering Journal, 2025)

Humic acid and ferrihydrite weaken Cd release and resupply in high geological background soil assessed by DGT-DIFS - Dongqin LI; Zhendong PENG; Chunyan LIU; Yongtao LI; Jinjin WANG; Zhichao WU; Qinghui LIU; Furong LI; Hanzhi SHI; Dian WEN; Huayi CHEN; Xu WANG; et al. (Pedosphere, 2025)

Dual modification of internal Co doping and surface Co nanoparticles decorating for boosting lithium storage of Si anode - Dian Yang; Chao Li; Lan Pan; Jizhang Chen; Wei Zhang; Qinghua Tian (Chemical Engineering Journal, 2025)

Vertical distribution and seasonal variations of dicarboxylic acids in urban PM2.5: Insights from multi-level observations on 600 m Canton tower in Guangzhou - Dian Ye; Shengzhen Zhou; Yuxuan Liang; Chunlei Cheng; Chenglei Pei; Yao Li; Min Gao; Xijing Sun; Siqi Chen; Jian Hang; Pingqing Fu; Shaojia Fan (Atmospheric Environment, 2025)

From mines to tombs: decoding the journey of turquoise artifacts at the Xingong site (1500-1300 BC), Beijing - Dian Chen; Ju Yang; Hongye Han; Jihao Zhang; Chao Li; Wugan Luo (Archaeological and Anthropological Sciences, 2025)

Review and prediction: Carbon emissions from the materialization of residential buildings in China - Xing Xiong; Xiaojun Li; Shaobo Chen; Dian Chen; Jinchen Lin (Sustainable Cities and Society, 2025)

Oxygen anion engineering suppressed active sites segregation for long-lasting electrocatalytic water oxidation - Yiwen Chen; Xiaoxia Chen; Chudi Ni; Shiyu Li; Dian Xiao; Meihuan Liu; Hui Su (Chemical Engineering Journal, 2025)

MXene functionalized cathodes, anodes, and separators for batteries - Jiakang Shi; Meng Du; Yihao Chen; Qian Li; Dian Xu; Guangxun Zhang; Huan Pang (Chemical Engineering Journal, 2025)

New insights into interfacial dynamics and mechanisms of biochar–derived dissolved organic matter on arsenic redistribution in Schwertmannite - Xiaofei Li; Tianfu Li; Yanfu Wei; Xiaohu Jin; Suresh C. Pillai; Jun Zhang; Dian Chen; Xiaolian Wu; Yanping Bao; Xueding Jiang; Hailong Wang (Environmental Pollution, 2025)

A self-designed pyrolysis-gasification-combustion pilot plant for rural solid waste disposal: The elucidation of emission factors - Wei Jiang; Dian Li; Hui Cai; Jiahui Yan; Yuanyao Ye; Jianxiong Kang; Qian Tang; Yongzheng Ren; Songlin Wang; Dongqi Liu; Zizheng Liu; Yiqun Chen (Atmospheric Pollution Research, 2025)

Engineering crystal network of supramolecular Oleogel via kinetical regulation for improved lutein bioaccessibility - Ao Zhang; Xin Wang; Ruimin Zhong; Cungang Li; Fangyuan Chen; Dian Zhang; Yong Cao; Yaqi Lan (Food Chemistry, 2025)

Overlooked non-homogeneous effects in solar gasification of biomass - Dian Zhong; Jieyang Li; Jun Li; Xin Chen; Kuo Zeng; Gilles Flamant; Haiping Yang; Hanping Chen (Chemical Engineering Journal, 2025)

Mitochondria-targeted delivery of zinc-coordinated resveratrol nanoparticles rescues the osteogenic potential of periodontal ligament stem cells compromised by inflammation for periodontal wound healing - Yu-Jie Tan; Xuan Li; Wen-Jie Zhang; Yu-Meng Cao; Jie-Kang Zou; Lin Jing; Dian Gan; Yu-Zhe Chen; Mei Xu; Ying An; Fa-Ming Chen; Xiao-Tao He; et al. (Chemical Engineering Journal, 2025)

Habitat changes of a small endemic euryhaline fish species in the northern margin of the South China Sea under the background of global warming - Jian Liao; Hao Chen; Jia-Yu Li; Gao-Cong Li; Xian Guan; Cai-Feng Liang; Yu-Song Guo; Zhong-Dian Dong; Zhong-Duo Wang (Frontiers in Marine Science, 2024)
Hainan medaka ( Oryzias curvinotus ) is a small euryhaline fish species native to the northern margin of the South China Sea. Our long-term field observations indicate a concerning decline in its wild resources. Climate change, an uncontrollable factor, has altered the species’ distribution pattern. In this study, we simulated the shifts in the species range of O. curvinotus during the Last Glacial Maximum (LGM), current, and the next one hundred year, and analyzed its habitat attributes. The results demonstrate that bio2 (mean diurnal range of temperature) is a crucial factor in shaping the species range of O. curvinotus . The simulation results reveal that the current habitats are located in the coastal areas of northern Vietnam, the northeastern Hainan Province, the coastal areas of Guangdong Province and Guangxi Zhuang Autonomous Region, and a few areas in Taiwan Province of China, covering a total area of 17.82×10 4 km 2 . Highly suitable habitats are mainly concentrated in the coastal areas of Hai Phong, Nam Dinh, and Thanh Hoa in northern Vietnam, the central part of Leizhou Peninsula, and the west coast of the Pearl River Estuary. For the tropical species Hainan medaka, the impact of the LGM was relatively minor, and there were extensive suitable habitats during historical times, including three refugia. Currently, only Refugium 2 near Guanghai Town, Taishan County, Jiangmen City, Guangdong Province in China remains, while the other two refugia have submerged below sea level. Future climate warming under different carbon emission levels is projected to cause a short-term expansion, followed by a relief in expansion. By 2100, the potential habitat area of O. curvinotus is slightly larger than the current scenario. It is noteworthy that under future climate warming scenarios, the highly suitable habitats will not migrate northward but will expand near the 21°N latitude. Overall, Hainan medaka is not expected to be threatened in the future. Our study provides long-term dynamic distribution data, which provides a theoretical basis for the long-term development and conservation management of Hainan medaka.

PinX1 plays multifaceted roles in human cancers: a review and perspectives - Dian You; Kaiwen Tong; Yuan Li; Ting Zhang; Yongqiang Wu; Ling Wang; Guangming Chen; Xiaoying Zhang (Molecular Biology Reports, 2024)

Denitrificimonas halotolerans sp. nov., a novel species isolated from UASB sludge treating landfill leachate - Shanhui Wang; Chu Yuan; Chengbin Xu; Ditian Li; Han Zhang; Jing Wang; Xin Wang; Yan Li; Dian Jiao; Siliang Yuan; Han Chen; Dongru Qiu (Antonie van Leeuwenhoek, 2024)

Synergistic effect of Bi and Fe for suppressing hydrogen evolution reaction (HER) and enhancing electrochemical nitrogen reduction reaction (eNRR) performance - Wenhua Guo; Yawei Li; Si-dian Li; Zongping Shao; Huili Chen (Chemical Engineering Journal, 2024)

Enabling stable high lithium storage of Si anode via synergistic effects of nanosized Fe3C and partially graphitized porous carbon - Dian Yang; Tianpeng Lv; Jian Song; Jizhang Chen; Li Hao; Qinghua Tian; Liang Cui (Chemical Engineering Journal, 2024)

Classifying seasonal patterns of clear-sky surface urban heat island worldwide and investigating impacts from surface energy variations - Kangning Li; Dian Lyu; Yunhao Chen; Jinbao Jiang (Sustainable Cities and Society, 2024)

Parameter analysis and optimization of multi-dimensional packed bed shrinkage model developed by phase field method for solar gasification of biomass - Hongyang Zuo; Kuo Zeng; Dian zhong; Jun Li; Huaqian Xu; Yongwen Lu; Yun Yu; Haiping Yang; Hanping Chen (Fuel, 2024)

Effect of vegetable oils on the thermal gel properties of PSE-like chicken breast meat protein isolate-based emulsion gels - Ke Li; Lin-Meng Wang; Bing-Bing Cui; Bo Chen; Dian-Bo Zhao; Yan-Hong Bai (Food Chemistry, 2024)

Comparative study of decoupled- and coupled-based predictive models for seismically-induced slope displacements during shallow crustal earthquakes - Mao-Xin Wang; Chen-Yang Zhang; Dian-Qing Li; Wenqi Du (Engineering Geology, 2024)

Deleterious variants in RNF111 impair female fertility and induce premature ovarian insufficiency in humans and mice - Chengcheng Song; Yingying Qin; Yan Li; Bingyi Yang; Ting Guo; Wenqing Ma; Dian Xu; Keyan Xu; Fangfang Fu; Li Jin; Yanhua Wu; Shuyan Tang; et al. (Science China Life Sciences, 2024)

Evolution and adaptation of terrestrial plant‐associated Plantibacter species into remote marine environments - Li Liao; Qilong Qin; Dian Yi; Qiliang Lai; Bolin Cong; Huiming Zhang; Zongze Shao; Jin Zhang; Bo Chen (Molecular Ecology, 2024)
Microbes are thought to be distributed and circulated around the world, but the connection between marine and terrestrial microbiomes remains largely unknown. We use Plantibacter , a representative genus associated with plants, as our research model to investigate the global distribution and adaptation of plant‐related bacteria in plant‐free environments, particularly in the remote Southern Ocean and the deep Atlantic Ocean. The marine isolates and their plant‐associated relatives shared over 98% whole‐genome average nucleotide identity (ANI), indicating recent divergence and ongoing speciation from plant‐related niches to marine environments. Comparative genomics revealed that the marine strains acquired new genes via horizontal gene transfer from non‐ Plantibacter species and refined existing genes through positive selection to improve adaptation to new habitats. Meanwhile, marine strains retained the ability to interact with plants, such as modifying root system architecture and promoting germination. Furthermore, Plantibacter species were found to be widely distributed in marine environments, revealing an unrecognized phenomenon that plant‐associated microbiomes have colonized the ocean, which could serve as a reservoir for plant growth‐promoting microbes. This study demonstrates the presence of an active reservoir of terrestrial plant growth‐promoting bacteria in remote marine systems and advances our understanding of the microbial connections between plant‐associated and plant‐free environments at the genome level.

Algae pyrolysis in alkaline molten salt: Products transformation - Jun Li; Kuo Zeng; Dian Zhong; Xin Chen; Ange Nzihou; Haiping Yang; Hanping Chen (Fuel, 2024)

The interaction of anti-inflammatory and anti-tumor components in the traditional Chinese medicine Solanum lyratum Thunb - Dian Zou; Xiaohua Li; Xinxin Zhou; Biaobiao Luo; Mohammad Omar Faruque; Sheng Hu; Jian Chen; Xuebo Hu (Natural Product Research, 2023)

Tissue-specific populations from amniotic fluid-derived mesenchymal stem cells manifest variant in vitro and in vivo properties - Nengqing Liu; Yi Cheng; Ding Wang; Hongmei Guan; Diyu Chen; Juan Zeng; Dian Lu; Yuanshuai Li; Yinghong Yang; Qian Luo; Lifen Zhu; Bin Jiang; et al. (Human Cell, 2023)
Amniotic fluid derived mesenchymal stem cells (AFMSCs), shed along the fetal development, exhibit superior multipotency and immunomodulatory properties compared to MSCs derived from other somatic tissues (e.g., bone marrow and fat). However, AFMSCs display heterogeneity due to source ambiguity, making them an underutilized stem cells source for translational clinical trials. Consequently, there is an urgent need to identify a method to purify the AFMSCs for clinical use. We found that the AFMSCs can be categorized into three distinct groups: kidney-specific AFMSCs (AFMSCs-K), lung-specific AFMSCs (AFMSCs-L), and AFMSCs with an undefined tissue source (AFMSCs-X). This classification was based on tissue-specific gene expression pattern of single cell colony. Additionally, we observed that AFMSCs-X, a minority population within the AFMSCs, exhibited the highest multipotency, proliferation, resistance to senescence and immuno-modulation. Our results showed that AFMSCs-X significantly improved survival rates and reduced bacterial colony forming units (CFU) in cecal ligation and puncture (CLP)-induced septic mice. Therefore, our study introduces a novel classification method to enhance the consistency and efficacy of AFMSCs. These subpopulations, originating from different tissue source, may offer a valuable and innovative resource of cells for regenerative medicine purposes.

Red mud with enhanced dealkalization performance by supercritical water technology for efficient SO2 capture - Zimeng Nie; Qun Zhao; Qilin Zhao; Yingjie Li; Dian Yang; Huaying Liu; Shupu Yang; Jie Li; Senlin Tian; Chen Li; Cheng Tie; Jianhong Huang; et al. (Journal of Environmental Management, 2023)

In situ growth of NH2-MIL-101 metal organic frameworks on biochar for glyphosate adsorption - Qi Wang; Kang-Ping Cui; Tong Liu; Chen-Xuan Li; Jun Liu; Dian-Chao Kong; Rohan Weerasooriya; Xing Chen (Chemosphere, 2023)

Solar pyrolysis of algae in molten salt for capacitive carbon preparation - Jun Li; Jing Peng; Kuo Zeng; Dian Zhong; Kang Xu; Vasilevich Sergey Vladimirovich; Ange Nzihou; Haiping Yang; Hanping Chen (Journal of Cleaner Production, 2023)

Self-assembled membranes modulate the active site of carbon fiber paper to boost the two-electron water oxidation reaction - Chen Ling; Dian Jin; Ruhong Li; Chaolin Li; Wenhui Wang (Chemical Engineering Journal, 2023)

Causal influences of salience/cerebellar networks on dorsal attention network subserved age-related cognitive slowing - Clive H. Y. Wong; Jiao Liu; Jing Tao; Li-dian Chen; Huan-ling Yuan; Mabel N. K. Wong; Yan-wen Xu; Tatia M. C. Lee; Chetwyn C. H. Chan (GeroScience, 2023)
Age-related cognitive slowing is a prominent precursor of cognitive decline. Functional neuroimaging studies found that cognitive processing speed is associated with activation and coupling among frontal, parietal and cerebellar brain networks. However, how the reciprocal influences of inter- and intra-network coupling mediate age-related decline in processing speed remains insufficiently studied. This study examined how inter- and intra-brain network influences mediate age-related slowing. We were interested in the fronto-insular salience network (SN), frontoparietal dorsal attention network (DAN), cerebellar network (CN) and default mode network (DMN). Reaction time (RT) and functional MRI data from 84 participants (aged 18–75) were collected while they were performing the Arrow Task in visual or audial forms. At the subject level, effective connectivities (ECs) were estimated with regression dynamic causal modelling. At the group level, structural equation models (SEMs) were used to model latent speed based on age and the EC mediators. Age was associated with decreased speed and increased inter-network effective connectivity. The CN exerting influence on the DAN (CN → DAN EC) mediated, while the SN → DAN EC suppressed age-related slowing. The DMN and intra-network ECs did not seem to play significant roles in slowing due to ageing. Inter-network connectivity from the CN and SN to the DAN contributes to age-related slowing. The seemingly antagonizing influences of the CN and SN indicate that increased task-related automaticity and decreased effortful control on top-down attention would promote greater speed in older individuals.

Estimating divergent forest carbon stocks and sinks via a knife set approach - Shitephen Wang; Keito Kobayashi; Satoru Takanashi; Chiung-Pin Liu; Dian-Rong Li; San-Wen Chen; Yu-Ting Cheng; Kai Moriguchi; Masako Dannoura (Journal of Environmental Management, 2023)

KMT2E Haploinsufficiency Manifests Autism-Like Behaviors and Amygdala Neuronal Development Dysfunction in Mice - Yuan-Jun Li; Chun-Yan Li; Chun-Yang Li; Dian-Xing Hu; Zhi-Bo Xv; Shu-Han Zhang; Qiang Li; Pei Zhang; Bo Tian; Xiao-Li Lan; Xiao-Qian Chen (Molecular Neurobiology, 2023)

Photo-thermal catalytic pyrolysis of waste plastics: Investigation into light-induced metal-support interaction - Haiping Yang; Shuai Yan; Dingding Yao; Hao Luo; Kuo Zeng; Jun Li; Dian Zhong; Haoyu Xiao; Hanping Chen (Fuel, 2023)

Solar pyrolysis of biomass - part II: The physicochemical structure evolution of char - Dian Zhong; Zheshao Chang; Kuo Zeng; Jun Li; Yi Qiu; Qiang Lu; Gilles Flamant; Haiping Yang; Hanping Chen (Fuel, 2023)

Retraction Note: Downregulation of long non-coding RNA TUG1 suppresses tumor growth by promoting ubiquitination of MET in diffuse large B-cell lymphoma - Hai Cheng; Zhiling Yan; Xue Wang; Jiang Cao; Wei Chen; Kunming Qi; Dian Zhou; Jieyun Xia; Na Qi; Zhenyu Li; Kailin Xu (Molecular and Cellular Biochemistry, 2023)

Heat-stress induced sesquiterpenes of Chrysanthemum nankingense attract herbivores but repel herbivore feeding - Dian Wen; Yaqin Guan; Li Jiang; Sumei Chen; Fadi Chen; Bin Liu; Ülo Niinemets; Yifan Jiang (Arthropod-Plant Interactions, 2023)

The characteristics and evolution of nitrogen in bio-oil from microalgae pyrolysis in molten salt - Kang Xu; Jun Li; Kuo Zeng; Dian Zhong; Jing Peng; Yi Qiu; Gilles Flamant; Haiping Yang; Hanping Chen (Fuel, 2023)

Multi-dimensional shrinkage models developed by phase field method for gasification of carbonaceous feedstock in packed-bed solar reactor - Hongyang Zuo; Kuo Zeng; Dian zhong; Jun Li; Yi Qiu; Huaqian Xu; Gilles Flamant; Haiping Yang; Hanping Chen (Fuel, 2023)

Effects of STAT3 Inhibitor BP-1-102 on The Proliferation, Invasiveness, Apoptosis and Neurosphere Formation of Glioma Cells in Vitro - Cheng-Chen Zhang; Ting Wu; Li Guan; Yu-Jue Wang; Rui-Qin Yao; Dian-Shuai Gao; Feng Li (Cell Biochemistry and Biophysics, 2022)

Development and perspectives of rapid detection technology in food and environment - Xue-Xia Jia; Shuang Li; Dian-Peng Han; Rui-peng Chen; Zi-Yi Yao; Bao-an Ning; Zhi-Xian Gao; Zhen-Chuan Fan (Critical Reviews in Food Science and Nutrition, 2022)

Biogeography of culturable marine bacteria from both poles reveals that ‘everything is not everywhere’ at the genomic level - Qi‐Long Qin; Zhi‐Bin Wang; Qian‐Qian Cha; Sha‐Sha Liu; Xue‐Bing Ren; Hui‐Hui Fu; Mei‐Ling Sun; Dian‐Li Zhao; Andrew McMinn; Yin Chen; Xiu‐Lan Chen; Yu‐Zhong Zhang; et al. (Environmental Microbiology, 2022)
Summary Based on 16S rRNA gene analyses, the same bacterial operational taxonomic units (OTUs) are common to both the Arctic and Antarctic oceans, supporting the concept ‘everything is everywhere’. However, whether the same OTUs from both poles have identical genomes, i.e. whether ‘everything is still everywhere’ at the genomic level has not yet been examined systematically. Here, we isolated, sequenced and compared the genomes of 45 culturable marine bacteria belonging to three genera of Salinibacterium , Psychrobacter and Pseudoalteromonas from both polar oceans. The bacterial strains with identical 16S rRNA genes were common to both poles in every genus, and four identical genomes were detected in the genus Salinibacterium from the Arctic region. However, no identical genomes were observed from opposite poles in this study. Our data, therefore, suggest that ‘everything is not everywhere’ at the genomic level. The divergence time between bacteria is hypothesized to exert a strong impact on the bacterial biogeography at the genomic level. The geographical isolation between poles was observed for recently diverged, highly similar genomes, but not for moderately similar genomes. This study thus improves our understanding of the factors affecting the genomic‐level biogeography of marine microorganisms isolated from distant locations.

An Investigation of Toxic Metal Levels (Pb, Cd, Cr, As, Hg) in Dried Porphyra and Laminaria Collected from Coastal Cities, China - Yan Chen; Yong-tao Liu; Fu-hua Wang; Dian Wen; Hui Yang; Xiao-li Zhao (Biological Trace Element Research, 2021)

Apatinib regulates the growth of gastric cancer cells by modulating apoptosis and autophagy - Xu Liu; Qiaoyu Zheng; Qiongfang Yu; Yan Hu; Yanmin Cheng; Zhaozhao Shao; Li Chen; Wenjie Ding; Dian Gao (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Cortical Hemodynamic Response Associated with Spatial Coding: A Near-Infrared Spectroscopy Study - Abiot Y. Derbie; Bolton Chau; Bess Lam; Yun-hua Fang; Kin-Hung Ting; Clive Y. H. Wong; Jing Tao; Li-dian Chen; Chetwyn C. H. Chan (Brain Topography, 2021)

Aloin Protects Against Blood–Brain Barrier Damage After Traumatic Brain Injury in Mice - Yao Jing; Dian-Xu Yang; Wei Wang; Fang Yuan; Hao Chen; Jun Ding; Zhi Geng; Heng-Li Tian (Neuroscience Bulletin, 2020)

RETRACTED ARTICLE: Downregulation of long non-coding RNA TUG1 suppresses tumor growth by promoting ubiquitination of MET in diffuse large B-cell lymphoma - Hai Cheng; Zhiling Yan; Xue Wang; Jiang Cao; Wei Chen; Kunming Qi; Dian Zhou; Jieyun Xia; Na Qi; Zhenyu Li; Kailin Xu (Molecular and Cellular Biochemistry, 2019)

Simulating the near-fault large velocity pulses of the Chi-Chi (Mw7.6) earthquake with kinematic model - Quanbo Luo; Xueliang Chen; Mengtan Gao; Zongchao Li; Zhen Zhang; Dian Zhou (Journal of Seismology, 2019)

Isolation and characterization of a waterlogging-responsive gene involved in ethylene biosynthesis in chrysanthemum - Zhiguo Zhang; Dongtao Luan; Gang Chen; Fang Xiao; Dongmei Yin; Dian Ni; Xiaorong Li; Lihong Qi (Acta Physiologiae Plantarum, 2018)

Improved application of tribenuron-methyl as a chemical hybridizing agent with forchlorfenuron for rapeseed hybrid breeding - Yong-Hong Li; Dian-Rong Li; Wu-Sheng Liang; Jian-Hua Tian; Jian-Chang Li; Hao Wang; Mao-Teng Li; Xu-Peng Guo; Wen-Jie Chen; Zhen-Lan Zhang; Fei Mao; Wei-Guo Zhao (Euphytica, 2017)

Erratum to: Activation of the ventral tegmental area increased wakefulness in mice - Huan-Xin Sun; Dian-Ru Wang; Chen-Bo Ye; Zhen-Zhen Hu; Chen-Yao Wang; Zhi-Li Huang; Su-Rong Yang (Sleep and Biological Rhythms, 2017)

Activation of the ventral tegmental area increased wakefulness in mice - Huan-Xin Sun; Dian-Ru Wang; Chen-Bo Ye; Zhen-Zhen Hu; Chen-Yao Wang; Zhi-Li Huang; Su-Rong Yang (Sleep and Biological Rhythms, 2017)

Molecular detection and genome characterization of porcine circovirus type 2 in rats captured on commercial swine farms - Shao-Lun Zhai; Sheng-Nan Chen; Wei Liu; Xiao-Peng Li; Su-Fang Deng; Xiao-Hui Wen; Man-Lin Luo; Dian-Hong Lv; Wen-Kang Wei; Rui-Ai Chen (Archives of Virology, 2016)

Facile microwave-assisted synthesis of benzimidazole scaffolds via Ugi-type three-component condensation (3CC) reactions - Gui-Ting Song; Zhi-Gang Xu; Dian-Yong Tang; Shi-Qiang Li; Zhi-Gang Xie; Hong-Liang Zhong; Zhi-Wei Yang; Jin Zhu; Jin Zhang; Zhong-Zhu Chen (Molecular Diversity, 2016)

Genome characterization and phylogenetic analysis of a lineage IV peste des petits ruminants virus in southern China - Xiao-Peng Li; Shao-Lun Zhai; Dong-Sheng He; Peng-Ju Guo; Dian-Hong Lv; Xiao-Hui Wen; Man-Lin Luo; Rui-Ai Chen; Wen-Kang Wei (Virus Genes, 2015)

Occurrence, sources, and ecological risks of PBDEs, PCBs, OCPs, and PAHs in surface sediments of the Yangtze River Delta city cluster, China - Ting Zhang; Wen-Long Yang; She-Jun Chen; Dian-Long Shi; Hu Zhao; Yi Ding; Ye-Ru Huang; Nan Li; Yue Ren; Bi-Xian Mai (Environmental Monitoring and Assessment, 2014)

Comparative genomics of the marine bacterial genus G laciecola reveals the high degree of genomic diversity and genomic characteristic for cold adaptation - Qi‐Long Qin; Bin‐Bin Xie; Yong Yu; Yan‐Li Shu; Jin‐Cheng Rong; Yan‐Jiao Zhang; Dian‐Li Zhao; Xiu‐Lan Chen; Xi‐Ying Zhang; Bo Chen; Bai‐Cheng Zhou; Yu‐Zhong Zhang (Environmental Microbiology, 2014)
Summary To what extent the genomes of different species belonging to one genus can be diverse and the relationship between genomic differentiation and environmental factor remain unclear for oceanic bacteria. With many new bacterial genera and species being isolated from marine environments, this question warrants attention. In this study, we sequenced all the type strains of the published species of G laciecola , a recently defined cold‐adapted genus with species from diverse marine locations, to study the genomic diversity and cold‐adaptation strategy in this genus. The genome size diverged widely from 3.08 to 5.96 M b, which can be explained by massive gene gain and loss events. Horizontal gene transfer and new gene emergence contributed substantially to the genome size expansion. The genus G laciecola had an open pan‐genome. Comparative genomic research indicated that species of the genus G laciecola had high diversity in genome size, gene content and genetic relatedness. This may be prevalent in marine bacterial genera considering the dynamic and complex environments of the ocean. Species of G laciecola had some common genomic features related to cold adaptation, which enable them to thrive and play a role in biogeochemical cycle in the cold marine environments.

Global MicroRNA Expression Profiling Reveals Differential Expression of Target Genes in 6-Hydroxydopamine-injured MN9D Cells - Li Li; Hui-Zhen Chen; Fang-Fang Chen; Feng Li; Meng Wang; Li Wang; Yun-Qing Li; Dian-Shuai Gao (NeuroMolecular Medicine, 2013)